THE HISTORY OF THE EMERGENCE OF GEOMETRY, THE RELATIONSHIP OF MATHEMATICS AND GEOMETRY - Abdurashitov Raxmatullo Abduxamitovich; Matematika Abdurashitov Raxmatullo; Abduxamitovich Matematika (American Journals, 2024)
This article addresses the issues of increasing the interest of primary school students in mathematics, the formation and development of logical thinking skills, increasing the effectiveness of education.
Keywords: Geometric shape, exhibition, didactic games, perimeter, surface, volume concept.